OPTIMIZATION OF PV MODULE WITH SINGLE-DIODE MODEL FOR TOKAT REGION - Cem Emeksiz Akif Akbulut Zafer Dogan Mehmet Akar (International Journal of Research Science and Management, 2017)
In this study single diode model of photovoltaic cell is is simulated with using all cell parameters for Tokat Region in TURKEY. Retscreen software and matlab were used to determine model parameters. Simulation studies were carried out with different irradiations and temperatures in Tokat Region. The output power, voltage and current characteristics of PV model are analyzied especially with taking the effect of temperature and irradiance. Komaes 140W PV module is referenced to analyze the presented model. Also Euclidean distance, Manhattan distance and Minskowski distance methods are used to determine distance from maximum panel power.